2021
DOI: 10.1073/pnas.2012900118
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous caregiving from birth to adulthood tunes humans’ social brain

Abstract: Mammalian young are born with immature brain and rely on the mother’s body and caregiving behavior for maturation of neurobiological systems that sustain adult sociality. While research in animal models indicated the long-term effects of maternal contact and caregiving on the adult brain, little is known about the effects of maternal–newborn contact and parenting behavior on social brain functioning in human adults. We followed human neonates, including premature infants who initially lacked or received matern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 120 publications
(147 reference statements)
1
25
0
3
Order By: Relevance
“…In support of this, a recent study showed that lacking bodily contact in the first weeks of life due to prenatal birth affected mother-infant synchrony (Yaniv et al, 2021 ). However, if additional skin-to-skin mother-newborn contact was provided, an increased mother-child synchrony was observed across development impacting the brain’s capacity to empathize with others in adulthood (Yaniv et al, 2021 ). These findings support that early sensory experiences shape the representation of one’s own body as a point of reference for interactions with the external physical and social environment with cascading effects on socio-emotional and cognitive development.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In support of this, a recent study showed that lacking bodily contact in the first weeks of life due to prenatal birth affected mother-infant synchrony (Yaniv et al, 2021 ). However, if additional skin-to-skin mother-newborn contact was provided, an increased mother-child synchrony was observed across development impacting the brain’s capacity to empathize with others in adulthood (Yaniv et al, 2021 ). These findings support that early sensory experiences shape the representation of one’s own body as a point of reference for interactions with the external physical and social environment with cascading effects on socio-emotional and cognitive development.…”
Section: Discussionmentioning
confidence: 90%
“…Thus atypical body-related multisensory integration could affect the development of body ownership and the malleability of one's own bodily representation, impacting higher-order social and cognitive processes, including the understanding of others' actions and emotions (Ropar et al, 2018). In support of this, a recent study showed that lacking bodily contact in the first weeks of life due to prenatal birth affected mother-infant synchrony (Yaniv et al, 2021). However, if additional skin-to-skin mother-newborn contact was provided, an increased motherchild synchrony was observed across development impacting the brain's capacity to empathize with others in adulthood (Yaniv et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…At birth, the higher cortical networks controlling the ANS increase their connectivity (Schlatterer et al, 2021 ) and, in low-risk newborns at around 1 day of age, coherence between electrocortical activity and brainstem-mediated autonomic tone, especially parasympathetic, can be easily detected (Mulkey et al, 2021 ). Social interactions, including skin-to-skin contact between mother and newborns, help increase ANS maturation as well as stress responsivity and circadian rhythms, in particular in preterm infants (Ulmer Yaniv et al, 2021 ).…”
Section: The Fetal Ans Development: the Search Of “Critical Windows”mentioning
confidence: 99%
“…These regions include the subcortical regions in the amygdala, nucleus accumbens (NAcc), and hypothalamus [56][57][58][59], and cortical regions in perception and action cortices [60], limbic cortices in the ventral anterior insula and cingulate cortex [61,62], and other association cortices in the ventromedial prefrontal cortex (vmPFC), ACC, and PCC [63,64]. Moreover, coordinated function and dopamine secretion within these regions is associated with improved social behavior in humans [65][66][67] and non-human mammals [68][69][70].…”
Section: Neural Basis Of Social Processing and How It Varies In Autismmentioning
confidence: 99%